2005
DOI: 10.1109/lpt.2005.856370
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized waveguide-integrated p-i-n photodetector with 120-GHz bandwidth and high responsivity

Abstract: A low-capacitance waveguide-integrated photodiode on InP with a minimized absorber length is presented. In order to maintain a high quantum efficiency, an optical matching layer exploiting mode beating effects is employed. Its optimization leads to a twofold enhanced external responsivity of 0.5 A/W at 1.55 µm wavelength in accordance with simulation. The reduced p-n junction capacitance enables 3 dB bandwidths up to 120 GHz mainly limited due to carrier transit time effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…of Uni-Travelling Carrier (UTC) type [13,14]. Our setup employed photodiodes originally developed for high speed telecommunication at 1.5 μm [15,16]. Unlike the UTC types of [13,14], these devices have a standard P-I-N structure.…”
Section: Terahertz Emitter: Waveguide Integrated Photodiode Antenna (mentioning
confidence: 99%
“…of Uni-Travelling Carrier (UTC) type [13,14]. Our setup employed photodiodes originally developed for high speed telecommunication at 1.5 μm [15,16]. Unlike the UTC types of [13,14], these devices have a standard P-I-N structure.…”
Section: Terahertz Emitter: Waveguide Integrated Photodiode Antenna (mentioning
confidence: 99%
“…For example submicron lithography is often required to fabricate the laterally tapered couplers [7]. Recently it has been shown that the critical taper technology can be replaced by exploiting mode-beating effects in coupled multimode waveguides [13][14][15][16][17]. Figure 3 shows a schematic of an evanescently coupled photodiode that utilizes a short multimode input waveguide with optical matching layers [14].…”
Section: A Optical Couplingmentioning
confidence: 99%
“…1 and 2) was integrated at the expense of half of the radio frequency (RF) photocurrent being lost. Details on the epitaxial layer stack and the fabrication process can be found in [5]. Using a cleaved fiber for the input, a responsivity of 0.24 A/W with a polarization dependent loss of only 0.2 dB was measured at 1.55 ptm wavelength.…”
mentioning
confidence: 99%
“…The InGaAs/InGaAsP heterostructure PDs with an intrinsic InGaAs absorption layer thickness of 200 nm were optimized to provide high responsivity [5]. A coplanar waveguide (CPW) transmission line connects the PDs in parallel and collects the electrical output signal.…”
mentioning
confidence: 99%